AB0596 Interferon-Γ release assay (T-SPOT.TB) in the diagnosis of tuberculosis infection in patients with behcet's disease: a single center experience in china. (15th June 2017) - Zheng, W; Wu, X; Chen, P; Zhao, L; Liu, J; Zhang, L; Liu, X; Zhao, Y; Zeng, X
Abstract : Background: In many aspects Behcet's disease (BD) is correlated with tuberculosis (TB). They may mimic each other on clinical manifestations. For example erythema nodosa, arthritis, gut lesions could be occurred in both disease and it is difficult for differential diagnosis. Some patients with newly-diagnosed BD were found to have active or latent or old TB and anti-TB therapy could relieve some of the symptoms. In etiology, it has been postulated that tubercle bacilli may act as a trigger of BD through the mechanism of molecular mimicking. Vice versa, defective cell-mediated immunity in BD patients may increase individual susceptibility of TB.It is extremely important to clarify TB existence or not in BD patients. Since BD patients commonly need glucocorticoid and immunosuppressant or even biologic agent such as anti-TNFa. And these medications may increase the risk of occurrence or flare of TB. But positive result of PPD shows little value in this special population due to acupuncture reaction in BD patients.In this pilot study, the values of interferon-γ release assay (T-SPOT-TB) in diagnosing active TB in BD patients were explored. Objectives: To investigate the diagnostic value of the T-SPOT.TB in BD patients complicated with tuberculosis infection. Methods: The clinical, radiology and laboratory data were collected and analyzed in 175 hospitalized BD patients from the Peking Union Medical College Hospital between January 2010 and March 2015. Statistical analysis was carried out using IBM SPSS version 20. Results: Of the 175 BD patients, the positive rate of tuberculosis infection in BD patients was 34.3%. The sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of the T-SPOT.TB test for the diagnosis of ATB were 87.5%, 73%, 36.8%, 98.3%, respectively. Positive likelihood ratio (PLR) and negative likelihood ratio (NLR) were 3.24 and 0.17. The median number of SFCs in the BD-ATB group was higher than that in the BD-LTB group and BD-OTB (p<0.001 and p=0.012). By ROC method, it was suggested that 70 SFCs act as a cutoff for diagnosing BD-ATB with the sensitivity, specificity, PPV, NPV, PLR and NLR were 87.5%, 85%, 24.6%, 98.5%, 5.79 and 0.15, respectively. The rates of LTB infection had no significant difference between BD patients and healthy controls. Agreement between T-SPOT.TB and TST in BD patients measured by the kappa coefficient was poor (kappa =0.37).Multiple logistic regression analysis revealed that BD patients with positive T-SPOT.TB had the highest likelihood of ATB (OR 11.93, 95% CI 2.108–67.508, p=0.005). Conclusions: T-SPOT.TB is a promising test in the diagnosis of BD complicated with tuberculosis infection, and higher number of SFCs may has a higher risk of ATB. Disclosure of Interest: None declared